Establishing a Literacy Tradition in Pesantren through Group Counseling at Pesantren Kyai Syarifuddin Lumajang - Hidayatulla, Moh. (Pesantren and Community Development Studies - Islamic Institute of Syarifuddin, Indonesia., 2024)
Pesantren Kyai Syarifuddin faces a significant challenge in cultivating reading interest among its students (santri), particularly those who previously showed little enthusiasm for reading. As a response, the institution has implemented group counseling services that provide a dynamic space for discussion and experience-sharing among santri. This study aims to analyze the implementation of group counseling in enhancing students' reading interest and to identify both the supporting and inhibiting factors in its application. The research adopts a qualitative approach, utilizing observation, interviews, and documentation as data collection techniques. The findings reveal that group counseling is effective in fostering reading interest among santri. Key supporting factors include student discipline, encouragement from counselors, and the students’ intrinsic motivation to learn. However, several inhibiting factors were also identified, such as limited participation from musyrifin (dorm supervisors), an unsupportive environmental context, and negative peer influence. The study concludes that group counseling plays a pivotal role in establishing a literacy tradition within Pesantren Kyai Syarifuddin and contributes significantly to enhancing students’ reading engagement. Nevertheless, to achieve optimal outcomes, it is essential to strengthen the active involvement of musyrifin and improve environmental conditions that support literacy development.